Blue laser welding of multi-layered AISI 316L stainless steel micro-foils. (December 2020) - Das, Abhishek; Fritz, Robert; Finuf, Mathew; Masters, Iain
Highlights: 20 layers of micro-foils (25 µm) welded to a 200 µm foil by a blue laser (~450 nm). Good-, over-, and under-welds were categorised based on joint characteristics. Epitaxial grains, heterogeneities, joint strength and failure modes were analysed. Feasibility of blue laser welding for multiple thin foils has been demonstrated. Abstract: This paper investigates the microstructural and mechanical behaviour of overlap micro-joints produced by a blue laser system with a wavelength of ~450 nm. AISI 316L stainless steel was used to produce assemblies of 20 layers of 25 µm micro-foil welded to a single 200 µm foil. The welding speed was varied from 6.5 m/min to 9.5 m/min in incremental steps of 1.0 m/min whilst the power was kept at a maximum output level of 500 W. The joints were analysed for fusion zone microstructure, crystallographic grain structure, microhardness distribution and lap shear and T-peel strengths. Interface width and penetration depth were used as key quality indicators to characterise the fusion zone microstructure. The welding speed modulation indicated that the penetration depth can be easily controlled during blue laser welding. The mechanical strength was evaluated by performing lap shear and T-peel tests. The results indicated that the blue laser welding can have a considerable impact on weld geometry and joint strength as it can reduce discontinuities in welded regions and generate good mechanical properties. This study demonstrated for the first time that the blue laser can be successfully implemented for multiple stack-up joining of stainless steel.